Development of Audio-Visual Media–Based Qur’anic Tilawah Learning at Al-Manar Klumpang Private Islamic Senior High School - Setiawan, Hasrian Rudi; Mayurida, Mayurida (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study aims to develop audio-visual media–based Qur’anic tilawah learning to improve students’ Qur’an recitation quality at Al-Manar Klumpang Private Islamic Senior High School. The study was motivated by the low proficiency of some students in makharijul huruf, tajwid rules, and recitation fluency. This research employed a Research and Development (RD) method using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects included Qur’an Hadith teachers and students of Al-Manar Klumpang Private Islamic Senior High School. Data were collected through observations, interviews, questionnaires, and performance tests of Qur’an recitation. The results indicated that the developed audio-visual learning media was feasible based on expert validation and positive responses from teachers and students. Furthermore, the implementation of the audio-visual media effectively improved students’ understanding of tajwid rules, accuracy of makharijul huruf, and fluency in Qur’an recitation. Therefore, the development of audio-visual media–based Qur’anic tilawah learning is considered effective and suitable as an innovative learning alternative in Islamic senior high schools.